حوار الحضارات في ظل القطب الواحد " قراءة من منظور النظرية الواقعية - مناصرية, ميمونة; حسني, هنية (جامعة الوادي - University of Eloued, 2017)
يعتبر موضوع حوار الحضارات من أهم الموضوعات التي أثارت جدلا واسعا بعد الحرب الباردة، إذ انقسم الباحثون والدارسون على مستوى العالم إلى فئتين، الأولى ترى أن صراع الحضارات سيكون ميزة الحقبة التي تلت الحرب الباردة ، بينما يرى طرف آخر أن الحوار هو من سيكون ميزتها ، ولكل طرف مبرراته التي بنى عليها مواقفه وأطروحاته وشكل من خلالها نظرياته ، إذ يرى الطرف الأول أن العالم أصبح يحتكم إلى قطب واحد تمثله قيم العولمة، بينما يرى الفريق الآخر بأن الحضارات إنما عليها أن تتحاور في سبيل إيجاد صيغ للتعاون الاقتصادي والسياسي بمختلف طرق الحوار النزيه، وبمختلف الوسائل المشروعة للتقريب بين مختلف الشعوب والأمم، دونما إهمال لحقوق وهوية أي طرف من الأطراف المتحاورة. ”The Dialog Among Civilizations” is one of the most important subjects that provoked wide controversy after the cold war, as researchers and scholars divided the world into two main categories; the first sees that the clash of civilizations would be the advantage of the era following the cold war, while the other side believes that dialog is to their advantage; and each party has his own justifications for his hypothesis which formed his theories. The first party claims that the world has become controlled by one pole represented by the values of globalization, while the second category finds that civilizations are to hold talks in order to find formulas for economic and political cooperation in various honest dialog ways, and with various legitimate means; thus bringing together peoples and nations, without neglecting rights and identity of any of the interlocutors .
مقال
Keywords: حوار الحضارات ، صراع الحضارات، النظرية الواقعية ، العولمة